MAJOR THEORIES OF LANGUAGE ACQUISITION - Shcherbukha , Roman; Vovk , Olena (Collection of scientific papers «ΛΌГOΣ», 2025)
This paper summarizes key language acquisition (LA) theories outlining their major hypothesis as well as critiques. It also presents an overview of central concepts related to LA.